On the storage stability of CaO biodiesel catalyst: hydration and carbonation poisoning - Soares Dias, A. P. (2021)
Lime based catalysts are reported to be active in oil alcoholysis, biodiesel production, but their sensitivity to moisture and atmospheric CO2 can hinder their use at the industrial level because it is suspected that they must be manipulated in a controlled atmosphere. The storage stability of lime catalyst was investigated for 180 days (temperature in the range 20-38 degrees C, relative humidity higher than 40%). Catalytic data showed biodiesel yields ranging from 87.5%, for the first day, to 79.4% for the 180th day, passing through a maximum of 91.5% obtained in the 30th day of storage. Hydration was mainly a surface process since the Ca(OH)(2) bulk phase was detected only at the end of the storage period. A catalyst stored for 10 mounts was successfully reactivated by annealing at 470 degrees C thus proving that CaO material is stable enough during storage and handling to be used as a biodiesel catalyst.